2020
DOI: 10.9734/ajrcos/2020/v5i430138
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of Campus Placement for Students Using Ensemble Voting Classifier

Abstract: Campus placement is a measure of students’ performance in a course. A forecasting method is proposed in this paper to predict possible campus placement of any institution. Data mining and knowledge discovery processes on academic career of students are applied. Supervised machine learning technique based classifiers are used for achieving this process. It uses an ensemble approach based voting classifier for choosing best classifier models to achieve better result over other classifiers. Experimental results h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They also proposed novel hybrid classifiers to gain accurate predictions of student performance. The results showed that the hybrid model outperformed the other classifiers in terms of accuracy (i.e., 81.67) precision (i.e., 79.62), recall (i.e., 75.86), and F-score (i.e., 77.69) in comparison to base classifiers and ensemble techniques applied in the same research [54].…”
Section: Comparison Of Applied Approach With Existing Approachesmentioning
confidence: 95%
See 1 more Smart Citation
“…They also proposed novel hybrid classifiers to gain accurate predictions of student performance. The results showed that the hybrid model outperformed the other classifiers in terms of accuracy (i.e., 81.67) precision (i.e., 79.62), recall (i.e., 75.86), and F-score (i.e., 77.69) in comparison to base classifiers and ensemble techniques applied in the same research [54].…”
Section: Comparison Of Applied Approach With Existing Approachesmentioning
confidence: 95%
“…The majority voting reflects more than 50% votes for the final decision; in unanimous voting, all classifiers develop an agreement for final decisions, whereas polarity voting considers the majority of votes to decide the final outcome. In this research, majority voting was used to combine classifiers because it provides better results in terms of accuracy, as indicated by prior research [53,54]. Moreover, three different algorithms including Naive Bayes, IBk, and ZeroR were used in this study for voting.…”
Section: Votingmentioning
confidence: 99%
“…Employability is the need vital no matter what the course picked by a student in high level training. The weakness of the consequence of guidance can be given a silver lining through the employability estimate model [14] [15]. Preparing today is fundamental for a merciless overall market that keeps on changing rapidly in light of mechanical advances.…”
Section: Literature Reviewmentioning
confidence: 99%